Peran Mahasiswa Sebagai Agen Satgas Bidang Perubahan Perilaku Covid-19 Melalui Penyebaran Infografis di Media Sosial - Fidrayani; Ivone Ayesha (CV Putra Publisher, 2023)
The increase in positive cases of Covid-19 in Indonesia has caused panic and fear among the people. Some people are already obedient to follow the health protocol from the government. However, there are still many people who turn a blind eye to the impact of this Covid-19. The holding of the Syarif Hidayatullah UIN KKN-DR, aims to enable students to help the community in raising awareness of the importance of maintaining health and cleanliness during the Covid-19 pandemic. The community needs maximum outreach about Covid-19. This led to a plan and determination to conduct outreach to the community on a regular basis. In view of Indonesia's condition which makes it impossible to hold gatherings, this outreach is carried out online by utilizing infographic media which are arranged briefly and clearly, which will later be distributed via social media. The method of activities carried out in this service program includes the preparation/socialization stage, the infographic distribution stage, and the evaluation stage. The social media used in distributing infographics is Instagram. Instagram is Dissemination carried out regularly, weekly in August and September 2021. The end result of this activity is the large number of netizens who view the infographics shared on social media. The purpose of holding this activity is so that people can increase awareness of the dangers or impacts of the spread of the Covid-19 virus.